Detection of self-complementary inverted repeats by single forward primer driven PCR - Kupi, Tünde; Deák, Tamás; Bisztray, György Dénes; Szegedi, Ernő (Acta Biologica Szegediensis, 2014)
Inverted repeat gene structures designed for silencing functional genes have been widely used both in academic and applied research. The correct orientations of such structures are usually validated with restriction analysis and/or sequencing. We speculated that the inverted repeat nature of such constructs can be shown by a simple PCR reaction with a single forward primer. To test this hypothesis five different constructs were established from grapevine sequences in a hairpin-intron style silencing system. We were able to amplify the appropriate products in each case. Thus a forward-primed PCR alone may be sufficient to prove the inverted repeat nature of the desired constructs.